Prospects of the development of aerospace complex of Ukraine in conditions of a new industrial revolution and integration with the European union - Matyushenko, I.; Rekun, A.; Pasmor, M.; Liakh, I.; Kupriyanova, V. (International Journal of Engineering and Technology, 2019)
The article examines the state of aerospace activity, the prospects of development and directions of increasing the competitiveness of aviation, rocket and space technology in the countries of the world and Ukraine in the context of the new industrial revolution and Ukraine’s in-depth integration with the EU. It has been established that today both the aviation industry and the rocket and space complex of Ukraine need to change the priorities of development, reorganization, restructuring. There also exists the need for significant investments in order to modernise the production on the basis of advanced production technologies of the new industrial revolution (Key Enabling Technologies / Advanced Manufacturing) together with converged technologies. It is proved that considering the interests of Ukraine’s national security under conditions of increased military threat, the air-space industry may, after a certain modernisation, play a leading role in the creation of a defence shield of the state. It is recommended that the Consultative working groups of the National Academy of Sciences of Ukraine, academic institutions and independent experts should be involved in forecasting and clarifying the priorities of the development of Ukraine’s aerospace complex in the context of its integration into the world and European aerospace.